EDUKASI DAMPAK PERNIKAHAN DINI TERHADAP RISIKO STUNTING DI KALANGAN SISWA SMPN 3 SUPPA - Makhrajani Majid; Armila Anar; Sari Murti; Rainer Schumacher Rafael B; Nur Aziza; Sulistiawati Sulistiawati; Sunita Sunita; Sunreanti Sunreanti; Putri Bintang Putri Bintang (Media Literasi Indonesia, 2025)
Early marriage is a significant risk factor that contributes to stunting, a condition of failure to thrive that can have long-term impacts on children's health and development. This educational program aims to increase students' understanding of SMPN 3 Suppa, Pinrang Regency about the relationship between early marriage and the risk of stunting. Activities are carried out through counseling which involves the delivery of educational material, interactive discussions to explore students' understanding in depth, as well as evaluation using pre-test and post-test. The material provided includes the definition of early marriage, stunting, health impacts, as well as the importance of optimal nutrition and parenting patterns. The evaluation results show a significant increase in student understanding, from 30% on the pre-test to 85% on the post-test. Interactive discussions also revealed cultural challenges and lack of awareness as supporting factors for early marriage. This program makes an important contribution to efforts to prevent stunting through youth education and is hoped to be the first step in involving the wider community, including parents and the surrounding community. With a comprehensive approach, this intervention can support the creation of a healthier and more productive young generation.